Message - Benatoui , Dr. Rima (Universal Journal of Pharmaceutical Research, 2023)
I salute all the UJPR team and its followers, The UJPR give chance to all authors to register, and sent their paper via their account, the severe examination of papers has confirmed with the moderate chance of accepted authors’ papers. Authors as have free of access to the site, after submission of the paper either research, review article, case report or short communication, that respect the format indicated in the author guidelines, the originality of the work is checked by the editor-in-chief and reviewers. Authors while preparing a research article almost fall into the trap of neglecting details in abstract, in the part of results and discussion authors compare their results with previous works and express their opinions about the results obtained without ignoring some parameters; in other hand, organization of the order of different parts should been respected. UJPR when receiving a paper appropriately presented and adopting an adequate subject, the affiliation of authors should been revealed, ethics if needed, and obviating plagiarism; that evaluated based on only copy and paste three consecutive words, even citing their source in the text have considered as plagiarism. UJPR as a scientific journal required a technical language facilitating its readability to reviewers who asked to focus only on scientific side of the paper. Reviewers have given sufficient time in case they accept to review the paper, as expected reviewers with their constructive feedback attempt to improve the presentation of the article. Publications in this journal have licensed under Creative Commons Attribution-Non-Commercial 4.0 international and authors should grant that the first publication of their works would be in UJPR. Greater opportunities of citation of the article, embodiment and development of the work obtained by dint of ‘Open Access’. As UJPR aim to interchange scientific knowledge and productive exchange, that, established in high read articles treating subjects as: entomotherapy, immunotherapy, pharmacotherapy, phytotherapy, indicating the wide fields treated during the previous issues.